A review of Tuberculosis (SIL) with special reference to Unani medicine - Salahuddin; Anjum, Rubi (Journal of Drug Delivery and Therapeutics, 2019)
Tuberculosis (TB) is an airborne infectious disease commonly affects the lungs. TB is a major global health problem which causes ill-health among millions of people each year. The disease is caused by infection via the lung with Mycobacterium tuberculosis, In Unani System of Medicine, tuberculosis is better known by the name of Diq or Sil.  Both the terms are considered synonyms. Sil being emaciation and Diq the low grade fever (Humma-e-Diq). Diq develops when the abnormal heat (Hararate ghariba) destroys the normal body fluids (Rutoobat-e-tabayee) of human body resulting in Hot & Dry (Har yabis) vital organs. This paper reviews the concept of tuberculosis, its etiology and management, described by ancient Unani scholars in detail.Keywords:   Tuberculosis, Sil,   Diq,   Hararate ghariba,   Rutoobate tabayee